ANALISIS STRATEGI DAN TAKTIK KOMUNIKASI MEDIA DIGITAL PADA INDUSTRI PERMESINAN ALAT BERAT GLOBAL - Bernado, Happy (JURNAL KOMUNITAS, 2025)
Companies need to communicate products to customers to differentiate product positions in the minds of the public, especially in the business to business (B2B) business model. Communication in this business model builds relationships between companies and customers through dialogue, interaction, education, persuasion, and information gathering. Digital media, as a new communication channel, is also utilized by companies in the machinery industry as B2B business model companies. This research focused on the observe of the digital communication patterns developed by five manufacturers of similar heavy equipment in the machinery industry. The approach applied was qualitative, with a case study method, and data collection was carried out through internet observations and documentation studies. The results of the study show that the five manufacturers implement various message strategies and use various social media communication channels, such as Instagram, Facebook, Linkedin, X, and Youtube, and optimize websites for communication. In addition, two of the five manufacturers also use blogs, community forums, and online stores to communicate in more detail with customers.